‘Feminism In Pursuit of Identity With Special Reference to Shakespeare’S Plays’: Exploring the Evolving Feminist Criticism of Shakespeare's Plays (Journal of Advances and Scholarly Researches in Allied Education, 2015)
In the world of work and politics some feminists tried todiscuss for dismantling all barriers against women while at the same timeapproving women’s “dual role”. After the 1970s the feminist approach toShakespeare developed with immense rapidity. A question arose whether Shakespeare was a feminist but the question wasdebated with great enthusiasm from both sides and has been accused of apatriarchal bias and as a sexist. The feminist criticism of Shakespearerecently divided into two incompatible ideological camps i.e., proto-feministsand patriarchal feminists.  However the recentfeminists have sought to escape from these ideological camps.  As a consequence it would appear that thewoman’s and man’s part are hardly essential and stable categories of identitybut contestable and changeable social constructs.